2022
DOI: 10.1177/03635465221128828
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Lateral Extra-articular Tenodesis on the Rate of Revision Anterior Cruciate Ligament Reconstruction in Elite Athletes

Abstract: Background: There is growing evidence that anterolateral procedures can reduce the risk of rerupture in high-risk recreational athletes undergoing primary anterior cruciate ligament (ACL) reconstruction (ACLR). However, this effectiveness has never been evaluated in elite athletes. Purpose: The purpose of this study was to evaluate the effectiveness of lateral extra-articular tenodesis (LET) in reducing revision rates in primary ACLR in elite athletes. Additionally, this study evaluated whether LET had a great… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(13 citation statements)
references
References 35 publications
0
13
0
Order By: Relevance
“…In 2012, 79% of patients received HT autograft while in 2016 that number dropped to 32%, with BPTB representing 61% of all ACLR grafts that year. The study of LET as an augment to HT ACLR represents an important innovation in response to inferior outcomes with HT alone and has consistently demonstrated lower failure rates than HT alone [12, 22, 23]. These results reflect why HT + LET acts more like BPTB than HT alone or other types of grafts in predictive models of graft failure/revision surgery.…”
Section: Discussionmentioning
confidence: 99%
“…In 2012, 79% of patients received HT autograft while in 2016 that number dropped to 32%, with BPTB representing 61% of all ACLR grafts that year. The study of LET as an augment to HT ACLR represents an important innovation in response to inferior outcomes with HT alone and has consistently demonstrated lower failure rates than HT alone [12, 22, 23]. These results reflect why HT + LET acts more like BPTB than HT alone or other types of grafts in predictive models of graft failure/revision surgery.…”
Section: Discussionmentioning
confidence: 99%
“…At 2 years of follow-up, in a pivoting non-elite sports population, Porter et al 33 found better patient-reported outcome measures (PROMs) in patients who had a LET. Recently, Borque et al 7 found that the addition of LET reduced the risk of undergoing revision by 2.8 times in elite athletes undergoing primary ACLR, suggesting the status as an elite athlete should be included as a potential indication for a LET, as they are at increased risk for ACL graft failure. In a previous study, 4 there was also no delay in RTP in cases with additional LET.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the femoral tunnel was the focus of this study. Second, recent research has placed emphasis on the anterolateral ligament (ALL) as a potential contributor to residual rotatory laxity following ACL injury [3, 4, 16, 21]. Conversely, some studies have suggested that the contribution of the ALL to rotatory knee laxity may be negligible [1, 2].…”
Section: Discussionmentioning
confidence: 99%